Peran Identitas Sosial terhadap Konten Publikasi Military Blogger Rusia di Media Sosial Telegram - Qintara, Dyandra Faza; Archellie, Reynaldo De (Universitas Negeri Surabaya, 2025)
Along with the cyber war and media manipulation under government control since the Russian military operation in Ukraine in February 2022, the Russian government has blocked public access to popular Western social media, such as Instagram, Facebook, and Twitter. As a result, a Russia-based social media called Telegram gained popularity and is used by pro-Russian military bloggers to spread awareness of the issue that was currently in focus among society. This research seeks to explain the motivation underlying the dissemination of information on @maryananaumova Telegram channel. By utilizing content analysis methods, authors identified recurring content patterns dominated by accusations and expressions of hatred towards Ukraine, as well as Russia’s image branding narrative throughout April-May 2023. The findings of this research demonstrate that Maryana's national identity and political affiliation exert influence in shaping the narrative on the Telegram channel, which tends to prioritize the dignity of pro-Russian groups.